Primary care and occupational medicine as team play – opportunities and challenges of sector-connecting care in the living environment Hausärztliche Versorgung und Arbeitsmedizin als Teamplay – Chancen und Herausforderungen der sektorenverbindenden Versorgung in der Lebenswelt - Kaifie-Pechmann, Andrea (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2025)
Cross-sectoral healthcare plays a central role in providing people with holistic and continuous care. In particular, the cooperation between general practitioners and occupational physicians plays a crucial role here.
CRIS-Team Scopus Importer:2025-03-21